2015 17th International Conference on Transparent Optical Networks (ICTON) 2015
DOI: 10.1109/icton.2015.7193338
|View full text |Cite
|
Sign up to set email alerts
|

Relay-assisted OFDM-based visible light communications over multipath channels

Abstract: Due to copyright restrictions, the access to the full text of this article is only available via subscription.In this paper, we investigate the performance of relay-assisted visible light communication (VLC) system over multipath channels. We consider an indoor environment where the ceiling light serves as the information source and a desk light helps the source forward the information to the destination. The VLC system is built on orthogonal frequency division multiplexing (OFDM) with either amplify-and-forwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Among the various possible strategies available for user-based relay assisted cooperation [ 19 , 20 ], in this paper we have adopted: the AF and DF schemes. In this case, the source transmits a packet (or symbol) in one time slot and the RN re-transmits it in the next time slot, which are then combined at the destination prior to decision making.…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various possible strategies available for user-based relay assisted cooperation [ 19 , 20 ], in this paper we have adopted: the AF and DF schemes. In this case, the source transmits a packet (or symbol) in one time slot and the RN re-transmits it in the next time slot, which are then combined at the destination prior to decision making.…”
Section: System Modelmentioning
confidence: 99%
“…OFDM VLC over frequency-selective indoor channels was analyzed in [ 19 ] providing the first analytical statistics for pure VLC relaying using amplify-and-forward (AF) or decode-and-forward (DF) relaying schemes. In [ 20 ] a relay based DC-biased optical OFDM (DCO-OFDM) VLC was investigated for two test cases using a desk lamp and a ceiling light lamp to provide optimal power allocation and improved bit error rate (BER) performance when employing relays compared to the direct transmission.…”
Section: Introductionmentioning
confidence: 99%
“…While the AF relay amplifies the received signal and forwards it to the end-user, the received signal is either decoded and forwarded by DF relays or compressed and forwarded by the CF relay to the destination. However, the cooperative version of DF protocols is known to be superior to the AF and DF protocols in terms of system performance and energy consumption [ 9 ]. However, this research work only considers SDF and IDF relay systems due its low complexity and simplicity for practical implementation in VLC.…”
Section: Introductionmentioning
confidence: 99%
“…This technology uses light emitting diodes (LEDs) to transmit data to the end users, this makes its potential implementation complexity and cost very low. Thanks to these reasons, VLC has become a very attractive technology and one of the most crucial green communication technologies for such applications [1]. Recent works have considered VLC as an alternative or complementary technology to communications [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that this system was efficient in terms of capacity. Improving the performance of the VLC systems by developing cooperation between light sources in indoor environment was investigated in [10]. The authors concluded that the achievable performance by deploying DF relaying was slightly higher than that accomplished by the implementation of AF relaying.…”
Section: Introductionmentioning
confidence: 99%